Preparation And Evaluation Of Sustained Release Matrix Tablets Of Propranolol Hydrochloride - SHANTVEER V. SALGER,; LINGARAJ S.DANKI,; SHIVANAND HIREMATH,; ABDUL SAYEED, (International Journal of Pharma and Bio Sciences, 2010)
The present study in the development of sustained release matrix tablets of anti-hypertensive drug propranolol hydrochloride. Hydroxypropyl methyl cellulose K100M used as a rate retarding polymer where as lactose and dibasic calcium phosphate are used as diluent. The effects of the proportion of the polymer and the influence of co-excipients like lactose and dibasic calcium phosphate on the release rate of drug was investigated. The results of the present study point out that the rate of propranolol hydrochloride release from HPMC K100M matrices are mainly controlled by the drug – HPMC ratio. When the influence of excipients on the release of drug was examined, the excipients lactose enhanced the release rate of propranolol hydrochloride, however the dibasic calcium phosphate (DCP) demonstrated slower release rate. The prepared sustained release matrix tablets were evaluated for various parameters like hardness, friability, uniformity of weight, uniformity of drug content, invitro drug release and short term stability studies. The dissolution t50% and t90% values for the co-excipients were in the order of lactose>dibasic calcium phosphate.